PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MATA PELAJARAN IPAS DI SDK SAWU - Mara Oktaviani Pio; Pelipus Wungo Kaka; Ermelinda Yosefa Awe; yosefina uge lawe (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The objective of this study is to determine the learning outcomes in the IPASsubject for Grade IV students at SDK Sawu through the implementation of theProblem Based Learning model. This research is a Classroom Action Research(CAR) using the Kemmis and Mc. Taggart design, which consists of four stages:planning, action, observation, and reflection. After the observation stage, reflectionis carried out to evaluate the strengths and weaknesses of the learning processand to plan improvements for the next cycle. This reflection serves as the basis forrefining the actions in the following cycle.The subjects of this study are 16 fourth-grade students at SDK Sawu, consisting of 10 female students and 6 malestudents. Data collection techniques include observation, learning outcome tests,and documentation. The instruments used are observation sheets for teacher andstudent activities as well as evaluation test items. Data were analyzed usingdescriptive quantitative analysis by calculating the average scores and thepercentage of class mastery.Based on the data analysis in Cycle I, the averagelearning result was 67.5%, with a classical completeness percentage of 37.5%,which falls under the